The Monetary Transmission Mechanism in Egypt - Al-Mashat, Rania (IMF Working Papers; Working Paper ;, 2007)
This paper examines the monetary transmission mechanism in Egypt against the background of the central bank's intention to shift to inflation targeting. It first describes the changing transmission channels over the last decade. Second, the channels are evaluated in a VAR model. The exchange rate channel plays a strong role in propagating monetary shocks to output and prices. Most other channels (bank lending, asset price) are rather weak. The interest rate channel is underdeveloped but appears to be strengthening since the introduction of the interest corridor in 2005, which bodes well for adopting inflation targeting over the medium term.